POLÍTICA LOCAL E CORONELISMO: UM ESTUDO SOBRE AS ELITES POLÍTICAS DE RIO CLARO - Bilac, Maria Beatriz (Caderno CRH, 2006)
Este artigo trata da temática das elites no Brasil, a partir de sua caracterização no processo de desenvolvimento brasileiro e dos vínculos que se estabelecem entre a dinâmica desse processo e seus agentes sociais. O objetivo específico é analisar, no conjunto das elites, um setor específico, as elites políticas, a partir da composição e recomposição desse grupo em uma cidade média do interior paulista - Rio Claro de 1900 ao golpe militar de 1964. PALAVRAS-CHAVE: Oligarquia, política local, elites políticas, coronelismo, poder. Local policy and the policy of the political leaders in rural areas: a study on the political elite in Rio Claro Maria Beatriz Bianchini Bilac This article deals with the topic of the elite in Brazil, from its characterization in the process of the Brazilian development and the bounds established between the dynamic of this process and its social agents. The specific aim is to analyze a specific sector, the political elite, within an elite, from the composition and re-composition of this group in an average city in São Paulo inland, Rio Claro, from the 1900’s up to the 1994 military intervention. KEY WORDS: Oligarchy, local policy, political elite, policy of the political chiefs in rural areas, power. Publicação Online do Caderno CRH: http://www.cadernocrh.ufba.br